KHADIJAH BINTI KHAWAILID RA SOSOK PEREMPUAN KARIER - Muhandis Azzuhri (Muwazah, 2009)
Imaging career women doesn’t always negative, women in Islamic law is allowed to work in accordance with their respective capabilities. The first figure of the Prophet’s wife Khadijah ra prove this. Khadija ra is the figure of a woman who is very tough work, international travel to Sham (Syria) and some other countries just to do business with colleagues spirit of honesty and openness. Khadija reimage as a career woman who could finance the universal mission of the Prophet at the beginning to the end of his mission the Prophet left a huge financial legacy that the Prophet could map the entire estate for the first time with the wife of a social solidarity fund for orphans, poor, submitted to the Baitul Mal and a few prophetic and apostolic interests. So, if there is a presumption that Islamic law forbids women work outside the home is actually contrary to the presumption of reality figure Mother of believers, Khadijah ra as a successful career woman in the running wheels of international and regional business in accordance with the principles of Islamic Syari’ah (law).